"Since both of us are using antiretrovirals, we have been supportive to each other": facilitators and barriers of pre‐exposure prophylaxis use in heterosexual HIV serodiscordant couples in Kisumu, Kenya. Issue 1 (12th December 2016) - Patel, Rena C; Stanford‐Moore, Gaelen; Odoyo, Josephine; Pyra, Maria; Wakhungu, Imeldah; Anand, Keerthana; Bukusi, Elizabeth A; Baeten, Jared M; Brown, Joelle M
Abstract : Introduction: Since 2015, the World Health Organization recommends pre‐exposure prophylaxis (PrEP) for all persons at substantial risk for HIV, including HIV‐uninfected partners in serodiscordant relationships in resource‐limited settings. As PrEP moves from clinical trials to real‐world use, understanding facilitators of and barriers to PrEP initiation and adherence is critical to successful PrEP implementation and rollout. Methods: We conducted 44 in‐depth individual or couple interviews with 63 participants (30 without HIV and 33 with HIV) enrolled in the Partners Demonstration Project in Kisumu, Kenya, between August and September 2014. The semi‐structured interviews discussed the following: 1) perceived advantages and disadvantages of antiretroviral therapy (ART)/PrEP; 2) reasons for accepting or declining ART/PrEP and 3) influence of prevention of transmission to partner or infant on ART/PrEP use. Transcripts from the interviews were iteratively analyzed using inductive content analysis. Results: Our study identified three key factors that may facilitate initiation of PrEP in this population. First, participants using PrEP felt reduced stress and increased trust in their HIV serodiscordant relationships. Second, greater community‐wide knowledge of PrEP was thought to likely increase PrEP acceptance. Third, greater education and counselling by providers on PrEP use was also considered to likely increase the adoption of PrEP. We also identified three key barriers to initiation of and adherence to PrEP. First, most participants who declined PrEP expressed doubts about the relative additional effectiveness of PrEP in combination with other prevention tools. Second, perceived stigma related to PrEP use was an important barrier to PrEP initiation. Third, many struggled with overcoming perceived side effects or logistical challenges of taking daily PrEP, particularly when they themselves were not ill. Conclusions: Leveraging the facilitators and overcoming barriers to PrEP uptake may enhance the successful rollout of PrEP among HIV serodiscordant couples in Kenya and other areas in sub‐Saharan Africa, thereby reducing sexual transmission of HIV. Further research focused on how best to provide counselling on combination HIV prevention tools in the context of PrEP use is a crucial next step to delivering PrEP.